Time of Day and a Ketogenic Diet Influence Susceptibility to SUDEP in Scn1aR1407X/+ Mice - Teran, Frida A.; Kim, YuJaung; Crotts, Megan S.; Bravo, Eduardo; Emaus, Katlynn J.; Richerson, George B. (Frontiers in Neurology, 2019)
Sudden unexpected death in epilepsy (SUDEP) is a major cause of mortality in patients with drug-resistant epilepsy. Most SUDEP cases occur in bed at night and are preceded by a generalized tonic-clonic seizure (GTCS) and. Dravet syndrome (DS) is a severe childhood-onset epilepsy commonly caused by mutations in the SCN1A gene. Affected individuals suffer from refractory seizures and an increased risk of SUDEP. Here, we demonstrate that mice with the Scn1aR1407X/+ loss-of-function mutation experience more spontaneous seizures and SUDEP during the early night. In DS mice we evaluate effects of long-term ketogenic diet (KD) treatment on mortality and seizure frequency. DS mice showed high premature mortality (44% survival by P60) that was associated with increased spontaneous GTCSs 1-2 days prior to SUDEP. KD treated mice had a significant reduction in mortality (86% survival by P60) compared to mice fed a control diet. Interestingly, increased survival was not associated with decreased spontaneous non-fatal seizures. Further studies are needed to determine how KD confers protection from SUDEP. Moreover, our findings implicate time of day as a factor influencing the occurrence of seizures and SUDEP. DS mice, though nocturnal, are more likely to have SUDEP at night, suggesting that the increased incidence of SUDEP at night in DS mice may not be solely due to sleep.